Microbiología de las infecciones osteoarticulares en niños atendidos en una clínica universitaria en la ciudad de Medellín, Colombia - Álvaro Hoyos-Orrego (Asociación Colombiana de Infectología, 2023)
Objective: the objective of the study was to describe the microorganisms, antimicrobial susceptibility, and diagnostic microbiology procedures in children with osteoarticular infections. Methods: This was a retro-prospective case series in children who consulted a university clinic in Medellín, Colombia, between 2010-2016, who had a culture-confirmed diagnosis. Results: Out of a total of 218 registered patients, we included 39 with microbiological confirmation. There were more males (27; 69,2%), and 71% cases occurred in >5 years old. The main microorganisms were Methicillin-Susceptible Staphylococcus aureus (MSSA) 53,8%, Methicillin-Resistant Staphylococcus aureus (MRSA) 20,5%, other gram-positive cocci 10%, Pseudomonas aeruginosa 5,1%, Enterobacter cloacae complex 2,5%, Haemophilus haemolyticus 2,5%, Mycobacterium tuber-culosis 2,5%, and Candida albicans 2,5%. The susceptibility of MSSA/MRSA to trimethoprim-sulfamethoxazole and vancomycin was 100%, and for clindamycin it was 100% and 87%, respectively. Bone tissue and bone secretion using conventional methods, bone pus or synovial fluid inoculated in a blood culture bottle, and synovial tissue were positive in 96%, 87,5% and 50%, respectively. The blood cultures were positive in 54%. In two patients only the blood cultures were positive. Conclusion: MSSA was the most frequent microorganism followed by MRSA. However, MRSA showed high susceptibility to trimethoprim-sulfamethoxazole, clindamycin, and vancomycin. The high positivity of primary cultures suggests the importance of always obtaining them. Although the positivity of blood cultures was lower, should always be included as part of microbiological studies